An Acoustic Platform for Single‐Cell, High‐Throughput Measurements of the Viscoelastic Properties of Cells. Issue 3 (16th December 2020) - Romanov, Valentin; Silvani, Giulia; Zhu, Huiyu; Cox, Charles D.; Martinac, Boris
Abstract: Cellular processes including adhesion, migration, and differentiation are governed by the distinct mechanical properties of each cell. Importantly, the mechanical properties of individual cells can vary depending on local physical and biochemical cues in a time‐dependent manner resulting in significant inter‐cell heterogeneity. While several different methods have been developed to interrogate the mechanical properties of single cells, throughput to capture this heterogeneity remains an issue. Here, single‐cell, high‐throughput characterization of adherent cells is demonstrated using acoustic force spectroscopy (AFS). AFS works by simultaneously, acoustically driving tens to hundreds of silica beads attached to cells away from the cell surface, allowing the user to measure the stiffness of adherent cells under multiple experimental conditions. It is shown that cells undergo marked changes in viscoelasticity as a function of temperature, by altering the temperature within the AFS microfluidic circuit between 21 and 37 °C. In addition, quantitative differences in cells exposed to different pharmacological treatments specifically targeting the membrane–cytoskeleton interface are shown. Further, the high‐throughput format of the AFS is utilized to rapidly probe, in excess of 1000 cells, three different cell lines expressing different levels of a mechanosensitive protein, Piezo1, demonstrating the ability to differentiate between cells based on protein expression levels. Abstract : Acoustic force spectroscopy is utilized to demonstrate high‐throughput characterization of the viscoelastic properties of adherent cells. Elasticity and fluidity measurements are resolved at the single‐cell level as a function of temperature, pharmacological treatments, and protein expression levels.